1972
DOI: 10.4315/0022-2747-35.5.295
|View full text |Cite
|
Sign up to set email alerts
|

The Propionic-Acid Bacteria-a Review

Abstract: This review, appearing in three parts, is concerned with the growth, metabolism, and miscellaneous metabolic activities of propionibacteria. The first section, presented here, deals primarily with nutritional requirements, substrate and product inhibition, physical factors, associative action of other microorganisms, and enumeration and isolation of propionibacteria. The nutrition of propionic-acid bacteria has been extensively investigated and the absolute requirements for their nutrition are known. Since pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 0 publications
3
34
1
Order By: Relevance
“…Cessation of growth and eventually cell death at pH values below 4 and 5 for LAB and PAB, respectively, are reported in literature (Hammes & Hertel, 2009;Hettinga & Reinbold, 1972). We observed that pH decreased below 4 within 24 h for LAB, except for L. brevis strains that did not acidify the medium below pH 6 and belonged to one of the best folate producing species in this study.…”
Section: Extracellular Folate Production and Metabolic Activity Of Lasupporting
confidence: 73%
See 2 more Smart Citations
“…Cessation of growth and eventually cell death at pH values below 4 and 5 for LAB and PAB, respectively, are reported in literature (Hammes & Hertel, 2009;Hettinga & Reinbold, 1972). We observed that pH decreased below 4 within 24 h for LAB, except for L. brevis strains that did not acidify the medium below pH 6 and belonged to one of the best folate producing species in this study.…”
Section: Extracellular Folate Production and Metabolic Activity Of Lasupporting
confidence: 73%
“…However, yields of the 3 tested strains were very low in a range from 0.058 to 0.115 mg mL À1 . Contrary, the genus Propionibacterium has been known for quite some time for their ability to produce vitamin B12 in large amounts (Hettinga & Reinbold, 1972). We however detected differences in the ability to produce vitamin B12 among different species.…”
Section: Intracellular Vitamin B12 Production In Lab and Pabmentioning
confidence: 63%
See 1 more Smart Citation
“…The propionibacteria are very sensitive to pH and usually require pH control because little growth occurs below pH 5.0 [3,7]. Lactate as carbon source has a clear advantage over glycerol and over sugarcane molasses when tight pH control cannot be implemented, as previously described [11], once it was shown that pH variation was faster when using BMG and BMSM in comparison to BML.…”
Section: Discussionmentioning
confidence: 89%
“…Propionic acid is the major product from the dicarboxylic acid pathway, also known as succinate pathway. This organic acid and its salts are able to inhibit microorganisms [1][2][3][4][5]. The prevailing view is that propionic acid disturbs the pH gradient across the cell membrane, an essential motive force for facultative anaerobes to transport nutrients and metabolites.…”
Section: Introductionmentioning
confidence: 99%